Phosphorylation-dependent association of human chromatin protein PC4 to linker histone H1 regulates genome organization and transcription. Issue 11 (7th June 2022) - Mustafi, Pallabi; Hu, Mingli; Kumari, Sujata; Das, Chandrima; Li, Guohong; Kundu, Tapas K
Abstract: Human Positive Coactivator 4 (PC4) is a multifaceted chromatin protein involved in diverse cellular processes including genome organization, transcription regulation, replication, DNA repair and autophagy. PC4 exists as a phospho-protein in cells which impinges on its acetylation by p300 and thereby affects its transcriptional co-activator functions via double-stranded DNA binding. Despite the inhibitory effects, the abundance of phosphorylated PC4 in cells intrigued us to investigate its role in chromatin functions in a basal state of the cell. We found that casein kinase-II (CKII)-mediated phosphorylation of PC4 is critical for its interaction with linker histone H1. By employing analytical ultracentrifugation and electron microscopy imaging of in vitro reconstituted nucleosomal array, we observed that phospho-mimic (PM) PC4 displays a superior chromatin condensation potential in conjunction with linker histone H1. ATAC-sequencing further unveiled the role of PC4 phosphorylation to be critical in inducing chromatin compaction of a wide array of coding and non-coding genes in vivo . Concordantly, phospho-PC4 mediated changes in chromatin accessibility led to gene repression and affected global histone modifications. We propose that the abundance of PC4 in its phosphorylated state contributes to genome compaction contrary to its co-activator function in driving several cellular processes like gene transcription and autophagy.